(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2026)
This article explores the disproportionate impact of climate change on young females in developing regions, specifically focusing on how environmental degradation intensifies traditional household responsibilities. As natural resources become scarce, girls are often pulled from classrooms to assist with water collection, fuel gathering, and domestic labor. This cycle not only jeopardizes their education and health but also reinforces systemic gender inequality. The study emphasizes the need for gender-sensitive climate policies that prioritize educational continuity and sustainable infrastructure.